Non-intubated vs. intubated video-assisted thoracoscopic surgery for the treatment of thoracic diseases: a systematic review and meta-analysis of propensity score-matched cohorts - Luo, Tao; Zhang, Yue; Xu, Bin-Wen; Zhang, Cheng-Cheng; Zhang, Li-Wen; Ran, Xin-Qiang; Fu, Mao-Yong (Frontiers in Surgery, 2025)
BackgroundVideo-assisted thoracic surgery (VATS) is commonly conducted under general anesthesia with tracheal intubation, which can lead to intubation-related complications. Consequently, non-intubated video-assisted thoracoscopic surgery (NIVATS) has gained increasing attention. However, debates persist regarding its safety and efficacy. This study aims to compare the safety and efficacy of NIVATS vs. intubated VATS (IVATS) in thoracic surgery.MethodsRelevant literature published up to October 2024 was collected from the Cochrane, PubMed, and Embase databases based on predefined inclusion criteria. Two reviewers independently screened these studies and extracted the pertinent data. After assessing the quality of the included studies, a meta-analysis was performed using Review Manager 5.3. Fixed-effects or random-effects models were utilized to synthesize the combined data.ResultsCompared with IVATS, NIVATS demonstrated shorter operative time [weighted mean difference (WMD) = −23.33 min; 95% confidence interval (CI), −33.62 to −13.04; P < 0.01], reduced anesthesia time (WMD = −29.10 min; 95% CI, −48.16 to −10.04; P < 0.01), shorter length of hospital stay (WMD = −0.46 days; 95% CI, −0.82 to −0.10; P = 0.01), and decreased chest tube drainage duration (WMD = −0.40 days; 95% CI, −0.71 to −0.09; P = 0.01). However, regarding the incidence of postoperative complications, contrary to previous meta-analyses, the NIVATS group exhibited a higher rate of postoperative complications (odds ratio = 1.87; 95% CI, 1.17–2.98; P = 0.008). No significant differences were observed between the groups in terms of intraoperative bleeding, the number of lymph nodes harvested, the number of N1 lymph nodes, the number of N2 lymph nodes, or postoperative length of hospital stay.ConclusionAlthough there were no significant differences between the two anesthesia methods concerning postoperative length of hospital stay, lymph node dissection, or intraoperative bleeding, NIVATS significantly reduced operative time, anesthesia time, length of hospital stay, and chest tube drainage duration. For highly selected patients, NIVATS may offer additional advantages. However, the increased postoperative complication rate associated with NIVATS compared with IVATS warrants further large, well-designed randomized trials.